Liquid Smoke Yield Grade 3, Grade 2 and Grade 1 from Five Different Types of Plants - Ita Merni; Aldo Kurniawan; Andi Yusuf (Jurnal Loupe, 2024)
This research was motivated by the lack of optimal use of leaves in forest plants, while there are many types of leaves in the forest. One use of leaves is to use them as raw material for making liquid smoke. This research was conducted to determine the yield of liquid smoke on forest plant species from their leaves. The research method used is the pyrolysis method with indirect combustion. This research was carried out by treating forest plant raw materials, namely kerai paying leaves (Filicium decipiens L.), bungur leaves (Lagerstroemia speciosa), mahogany leaves (Swietenia macrophylla King), teak leaves (Tectona grandis) and sungkai leaves (Peronema canecens Jack). The results of the research showed that the results of liquid smoke from the 5 types of plant leaves, namely sungkai leaves, had the highest grade 3 yield of 23.83% and the lowest grade 3 yield, namely mahogany leaves, of 17.81%. In grade 2 sungkai leaves the highest percentage was 21.12% and mahogany leaves had the lowest yield with a percentage of 16.18%. Meanwhile, in grade 1, sungkai leaves have the highest yield percentage of 19.33% and mahogany leaves have the lowest yield, namely 15.03%.